Pembelajaran Seni Budaya (Tari Kreasi Zapin Sekampung) Di SMAN 3 Siak Hulu Provinsi Riau TA.2023/2024 - Iqlima Rohayanina; Nurmalinda Nurmalinda (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The aim of this research is to determine the learning of Cultural Arts (Zapin Sekampung Creative Dance) at SMAN 3 Siak Hulu FY 2023/2024. This research uses Hadiansyah's theory (2022). In this research the author used descriptive qualitative research methods. The research subjects were 36 Arts and Culture Teachers and Class X students. Data collection techniques using observation, interviews and documentation. The results of the research show that Cultural Arts Learning (Zapin Sekampung Creative Dance) at SMAN 3 Siak Hulu FY 2023/2024 can be seen from the Independent Curriculum components, especially those prepared through teaching modules which have several indicators including: Learning Achievement (CP) is learning competence that must be achieved by students at the end of each learning phase, Learning Objectives (TP) are a description of the achievement of knowledge, skills and attitudes obtained in learning activities, Learning Objectives Flow (ATP) is a learning phase for students in achieving learning, Teaching Tools are materials teaching in the form of learning material as the main material for discussion, Learning Assessment is the process of collecting and processing information data as a learning need, Student Worksheets (LKPD) are student learning sheets in the form of tasks given by educators referring to the basic competencies to be achieved. Learning activities consist of routine and scheduled activities based on structured lesson content according to what has been prepared through Teaching Modules that have been designed by the Arts and Culture teacher.